Parents Variables and Their Involvement in Community-School Partnership on Pupils Learning Outcomes in Lower Primary Schools In Southwestern Nigeria. - Adediran, V. O.; Adeyemi, B. A. (Advances in Social Sciences Research Journal, 2016)
The study determined the levels of parent-school and school-community partnerships in lower primary school in Southwestern Nigeria, and examined the joint influence of parents’ characteristics (age, gender, levels of education and the level of their involvement in community-school partnerships) on pupils’ learning outcomes in Southwestern Nigeria. These were with a view to providing information on the roles of parent-school and community-school partnerships in enhancing learning outcomes of lower primary school pupils in Southwestern Nigeria. The study employed survey research design. The population for the study comprised lower primary school class III pupils, their parents, teachers and head teachers in Southwestern Nigeria. The sample which comprised 1,980 participants (900 primary III pupils, 90 primary III teachers, 90 head teachers and 900 parents of the pupils) was selected using multi-stage sampling technique. Four research instruments were used for data collection, namely: Test of Numeracy and Verbal Reasoning (TNVR), Social Attribute Checklist (SAC), Parents-School Partnership Questionnaire (PSPQ), and Community-School Partnership Practices Questionnaire (CSPPQ). The data collected were analyzed using, simple percentages, chi-square statistics and multiple regression analyses. The results showed that the levels of parent-school partnerships in lower primary education in Southwestern Nigeria were high (13.4%), moderate (64.1%), and low (22.4%), while those of school-community partnerships were high (9.0%), moderate (49.6%) and low (41.4%). Also there was no joint influence of parents’ characteristics (age, gender, level of education and their involvements in school-community partnerships) on social behaviour (F = 16.480, p > 0.05) whereas there was significant joint influence of the characteristics on pupils’ academic achievement (F = 2.606; p 0.05). The study concluded that parent-school and community-school partnerships had significant roles to play in enhancing learning outcomes of lower primary school pupils in Southwestern Nigeria.